Investigating the factors that affect academic performance of first year Psychology and Sociology students at the University of Namibia (Journal for Studies in Humanities and Social Sciences, 2020)
Stress is inevitable; it has become part of students’ lives as they work hard and compete at every stage of their academic careers. Students’ academic performance at tertiary institutions is affected by stress and their levels of motivation. The purpose of this study was to explore the effect of stress, motivation and teaching styles of lecturers on first year students’ academic performance. This is because reducing students’ stress levels and finding ways to increase their levels of motivation would result in better academic performance; a greater understanding of factors underlying academic stress is believed to lead to improved stress management strategies and academic success; and this understanding would facilitate the development of effective counselling modules and intervention strategies by student counsellors to help students alleviate stress. The sample consisted of students from the University of Namibia’s main campus in Windhoek (n=321). The study questionnaire collected data on the biographical details, motivation, perceived stress, teaching style experienced and academic performance of first year Psychology and Sociology students of 2018. This study found that extrinsic motivation, a motivation and perceived stress negatively affected academicperformance. Teaching style (facilitating expert style) positively affected motivation to know, motivation to achieve and extrinsic motivation. Motivation to know and motivation to achieve reported a positive effect on academic performance.
Keywords: perceived stress; motivation; teaching style; academic performance